Isolation of ubiquitinated substrates by tandem affinity purification of E3 ligase-polyubiquitin-binding domain fusions (ligase traps) - Mark, Kevin G (Nat Protoc, 2016)
Ubiquitination is an essential protein modification that influences eukaryotic processes ranging from substrate degradation to nonproteolytic pathway alterations, including DNA repair and endocytosis. Previous attempts to analyze substrates via affinity purification approach in which ubiquitin ligases are fused to a polyubiquitin-binding domain, which allows the isolation ubiquitin. By using this protocol, ubiquitinated substrates that are specific for a given ligase can be isolated for mass spectrometry or western blot analysis. After cells have been collected, the described protocol can be completed in 2–3 d.